ANALISIS LAPORAN KEUANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) INDUSTRI TAS DAN SEPATU NEW HUNTERIA DENGAN PENDEKATAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAKEMKM) - Mishelei Loen, SE., M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
Micro, Small and Medium Enterprises (MSMEs) are businesses that have the same owner and manager, capital is provided by an owner or a small group of capital owners. This study examines the New Hunteria Micro Small and Medium Enterprises (MSMEs) in the Depok city. This research uses qualitative research with descriptive type. Data collection in research was obtained through interviews and observations. Based on the results of the study, the Hunteria New Bag and Shoes Industry researchers can conclude that the financial statements made by Micro, Small and Medium Enterprises (MSMEs) are not yet in accordance with the Financial Accounting Standards for Micro, Small and Medium Financial Accounting Standards (SAK EMKM). The New Hunteria Bag and Shoes Industry only makes financial records in the form of records of raw material purchases, sales, employee salaries, and other costs